Niche partitioning of intertidal seagrasses: evidence of the influence of substrate temperature. Issue 4 (14th December 2017) - Campbell, Marnie L.; Heppenstall, Lara D.; Hendry, Rebecca; Martin, Ross; Sørensen, Stine; Rubenstein, Ashley N.; Hewitt, Chad L.
Summary: The influence of soil temperature on rhizome depths of four intertidal seagrass species was investigated in central Queensland, Australia. We postulated that certain intertidal seagrass species are soil temperature‐sensitive and vertically stratify rhizome depths. Below‐ground vertical stratification of intertidal seagrass rhizome depths was analysed based upon microclimate (soil temperature) and microhabitat (soil type). Soil temperature profiles exhibited heat transfer from surface layers to depth that varied by microhabitat, with vertical stratification of rhizome depths between species. Halodule uninervis rhizomes maintain a narrow median soil temperature envelope; compensating for high surface temperatures by occupying deeper, cooler soil substrates. Halophila decipiens, Halophila ovalis and Zostera muelleri rhizomes are shallow‐rooted and exposed to fluctuating temperatures, with broader median temperature envelopes. Halodule uninervis appears to be a niche specialist, with the two Halophila species considered as generalist niche usage species. The implications of niche use based upon soil temperature profiles and rhizome rooting depths are discussed in the context of species' thermal tolerances and below‐ground biomass O2 demand associated with respiration and maintenance of oxic microshields. This preliminary evidence suggests that soil temperature interaction with rhizome rooting depths may be a factor that influences the distribution of intertidal seagrasses.